Whole genome sequencing of Mycobacterium bovis to obtain molecular fingerprints in human and cattle isolates from Baja California, Mexico. (October 2017) - Sandoval-Azuara, Sarai Estrella; Muñiz-Salazar, Raquel; Perea-Jacobo, Ricardo; Robbe-Austerman, Suelee; Perera-Ortiz, Alejandro; López-Valencia, Gilberto; Bravo, Doris M.; Sanchez-Flores, Alejandro; Miranda-Guzmán, Daniela; Flores-López, Carlos Alberto; Zenteno-Cuevas, Roberto; Laniado-Laborín, Rafael; et al.
Abstract: Objectives: To determine genetic diversity by comparing the whole genome sequences of cattle and human Mycobacterium bovis isolates from Baja California. Methods: A whole genome sequencing strategy was used to obtain the molecular fingerprints of 172 isolates of M. bovis obtained from Baja California, Mexico; 155 isolates were from cattle and 17 isolates were from humans. Spoligotypes were characterized in silico and single nucleotide polymorphism (SNP) differences between the isolates were evaluated. Results: A total of 12 M. bovis spoligotype patterns were identified in cattle and humans. Two predominant spoligotypes patterns were seen in both cattle and humans: SB0145 and SB1040. The SB0145 spoligotype represented 59% of cattle isolates ( n  = 91) and 65% of human isolates ( n  = 11), while the SB1040 spoligotype represented 30% of cattle isolates ( n  = 47) and 30% of human isolates ( n  = 5). When evaluating SNP differences, the human isolates were intimately intertwined with the cattle isolates. Conclusions: All isolates from humans had spoligotype patterns that matched those observed in the cattle isolates, and all human isolates shared common ancestors with cattle in Baja California based on SNP analysis. This suggests that most human tuberculosis caused by M. bovis in Baja California is derived from M. bovis circulating in Baja California cattle. These results reinforce the importance of bovine tuberculosis surveillance and control in this region.